Methodology of al-Biruni (973-1048) and al-Faruqi (1921-1986) in the study of religions : a comparative analysis - Siti Nurleha bt Saffie (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The interest in the study of religions continues to flourish in this age of globalisation. Muslim scholars have pioneered the effort and significantly contributed works, references, and methodologies in the study of religions. Examples include Ibn Nadim, Ibn Hazm, Shahrastani, al-Jahiz, al-Biruni and many others. Western scholars however, started their interest in the study of religions much later in the 19th century. As a result of such interest, the modern Western scholars have introduced a number of methodologies and approaches in the study of religions such as phenomenological, dialogical, sociological, and psychological. However, there are debates concerning the best methodology that agrees to principles of objectivity and scientific accuracy. In this regard, there is a need to search for a methodology that observes principles of objectivity and scientific accuracy from among the Muslim scholars of religion. Al-Biruni and al-Faruqi are examples of Muslim scholars who have vested their interest in the study of religions. This study therefore aims to highlight the methodology in the study of religions by referring to both scholars who share similarities as well as differences. The study adopts the qualitative method for gathering as well as analysing of data. The method is mainly based on library research, analysis of data, and textual analysis of al-Biruni's and al-Faruqi's works in the study of religions. In addition to these, aspects of their lives and thoughts are also studied thoroughly. This study concludes that al-Biruni and al-Faruqi are different in terms of their context, the religions that they studied as well as their methodologies. However, it is also found that both scholars are similarly concerned with scientific accuracy and the objective study of religions. They offer alternative of methods in the study of religions, which comply with systematic and empirical study. Their methodologies can be emulated in order to improve inter-religious understanding and thus overcome conflicts among religions of the world.